Childhood Stunting as a Public Health Problem and its Prevention Interventions: A Literature Review - Atalia Pili Mangngi (International Journal of Health and Medicine, 2026)
Stunting is a major public health problem that reflects chronic malnutrition and adversely affects children’s physical growth, cognitive development, and future productivity. The first 1,000 days of life represent a critical window during which stunting develops and determines long-term health outcomes. This study aims to review evidence on the determinants of childhood stunting and the effectiveness of prevention interventions within public health policy frameworks in Indonesia.A literature review was conducted using peer-reviewed articles, policy documents, and national reports published in the last decade. The literature was analyzed to identify key risk factors, intervention strategies, and policy impacts on stunting reduc-tion.The findings show that stunting is primarily driven by inadequate dietary intake, low socioeconomic status, limited caregiver nutrition knowledge, and poor access to health and sanitation services. National data indicate a decline in stunting prevalence in Indonesia from 24.4% in 2021 to 21.6% in 2022. Evidence consistently highlights that integrated interventions targeting the first 1,000 days of life, including maternal nutrition improvement, breastfeeding promotion, appropriate complementary feeding, and multisectoral collaboration, are effective in reducing stunting.In conclusion, reducing childhood stunting requires sustained, integrated, and policy-based interventions that prioritize early-life nutrition to improve human capital and support long-term national development.